Penggunaan Bahasa Erotisme dan Pemajasan dalam Kumpulan Cerpen 1 Perempuan 14 Laki-laki - Anggraini, Tri Riya (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The success of a real literary work can not be separated from the aesthetic value that is owned by a literary work. The aesthetic value can be viewed in terms of the use of language style. Therefore, as a supporter of the aesthetic value of a literary work, required the use of a variety of style, one element of eroticism is seen to pose a greater sense of real value and pemajasan to beautify the intended meaning. The study which is based on the short story collection 1 Perempuan 14 Laki-Laki by Djenar Maesa Ayu and others, aims to describe how to use the language of eroticism as well as in the book collection pemajasan 1 Perempuan 14 Laki-Laki by  Djenar Maesa Ayu and others. The method selected for this study was descriptive qualitative method. The most dominant figure of speech is an affirmation, an affirmation figure of speech itself is the most widespread is the figure of speech repetition. The next domination demonstrated through comparison figure of speech.